Platelet count as a predictor of outcome of hospitalized patients with community-acquired pneumonia at Zagazig University Hospitals, Egypt - Adel H. A. Ghoneim; Mohammad A. Mohammad; Mohammad A. Elghamrawy; Sameh Embarak (The Egyptian Journal of Bronchology, 2020)
Abstract Background Platelets play an essential role in both coagulation system and the host immune defenses against infection including community-acquired pneumonia (CAP). This work aimed to study the possibility of using platelet count as an additional criterion to predict the outcome of hospitalized patients with CAP. Results This prospective cohort study included 250 patients hospitalized with CAP. According to platelet count at admission, 15 (6%) patients showed thrombocytopenia (group I) and 202 (80.8%) showed normal platelet count (group II), while 33 (13.2%) patients showed thrombocytosis (group III). CAP patients with thrombocytosis had more significant respiratory complications including lung abscess (p = 0.02), empyema (p < 0.001), and pleural effusion (p = 0.01). Severe sepsis and septic shock were significantly encountered among CAP patients with thrombocytopenia (p = 0.02 and 0.03, respectively). CAP patients with thrombocytopenia significantly needed mechanical ventilation either invasive (p = 0.017) or even non-invasive (p = 0.047). Both CAP patients with thrombocytopenia or thrombocytosis had significant 30 days readmission (p = 0.034) and significant 30 days mortality (p = 0.016) when compared to CAP patients with normal platelet count. Both thrombocytopenia (p = 0.012) and thrombocytosis (p = 0.029) were independent predictors of 30 days mortality among hospitalized patients with CAP. Conclusions Both thrombocytosis and thrombocytopenia are linked to adverse outcomes among hospitalized patients with CAP.